Dampak Krisis Finansial Amerika Serikat Terhadap Perekonomian Asia - Teguh Sihono (Jurnal Ekonomi dan Pendidikan, 2009)
The world recession that in there years be finished because financial crisis which triggered by housing credit crisis (subprime-mortgage) in the United State of America. Financial crisis in United State involved financial institute of large scale in United State, Europe, and Japan. Clogged credit as big as US$ 1,8 quintillion cause loss US$ 300 billion and in the direct to US$ 1 quintillion number. Clogged credit to lead to credit crunch that cause real sector. The condition of financial institute is illiquid, Federal reserve rate was high constant, weak demand, decrease production, oil price attack on the flank until United State economy suffered stagnation.This financial crisis in serious condition it by world oil price that highly, rise it commodity price, fall consumption, Fed rate that high, production fall, inflation pressure, unemployment rising, fall of stock price, fall growth economy, until United State economy experience stagflation. Nothing progress state were prepared help really, they submitted to United State alone contend recession deserving them.